Establishment of Unipolar Localization of IcsA in Shigella flexneri 2a Is Not Dependent on Virulence Plasmid Determinants - Sandlin, Robin C. (American Society for Microbiology, 1999)
Unipolar localization of IcsA on the surface of Shigella flexneri is required for efficient formation of actin tails and protrusions in infected eucaryotic cells. Lipopolysaccharide (LPS) mutations have been demonstrated to affect either the establishment or the maintenance of IcsA in a unipolar location, although the mechanism is unknown. In order to analyze the contribution of virulence plasmid determinants on the unipolar localization of IcsA, we examined the localization of IcsA expressed from a cloned plasmid copy in two different genetic backgrounds. The localization of IcsA was first examined in a virulence plasmid-cured derivative of the wild-type S. flexneri 2a isolate 2457T. This approach examined the contribution of virulence plasmid-borne factors, including the previously identified virulence plasmid-borne protease that is responsible for cleaving IcsA in the outer membrane and releasing the 95-kDa secreted form from the cell surface. IcsA localization in a related but nonpathogenic Escherichia coli strain expressing LPS of the O8 serotype was also examined. IcsA surface presentation in both of these genetic backgrounds continued to be unipolar, demonstrating that virulence plasmid-borne determinants are not responsible for unipolar localization of IcsA. The unipolar localization of IcsA in the E. coli background suggests that a common pathway that allows IcsA to be spatially restricted to one pole on the bacterial cell surface exists in Shigella and E. coli.